GuttaFlow Bioseal versus Monocone Obturation Technique. A Scanning Electron Microscopy Study. - Nordin, Nuradlin; Embong, Siti Nur Hanie; Kharuddin, Azrul Fazwan; Mahdan, Mohd Haidil Akmal; Mustaffa, Musliana (2019)
Introduction: The adaptation of GuttaFlow Bioseal in root canal system is poorly understood due to the limited evidence and further investigation may provide better insights. This study compared sealing ability, extrusion of root filling materials beyond apical foramen and duration of time required for obturation between GuttaFlow Bioseal and monocone obturation techniques. Materials and methods: The root canals of twenty single-rooted mandibular premolars were prepared using Hyflex CM rotary files (Coltène/Whaledent). Then, the samples were equally divided into two groups; GuttaFlow Bioseal and monocone. The roots were sectioned at perpendicular direction to obtain 3 root segments; coronal 1/3, middle 1/3 and apical 1/3. All resected roots were mounted on brass stubs, sputter-coated with thin gold coating and observed under scanning electron microscope (Zeiss EVO50, Germany) at 20x magnification. All images were transferred to the SketchAndCalc Area Calculator software and the root canals sealed with root filling materials were evaluated. The data was analysed with SPSS version 23.0. Results: The mean score of root canals sealed with root filling materials ranged from 81.90 to 89.31 with no statistically significant difference at any level of evaluation. The mean proportion of extrusion of root filling materials between GuttaFlow Bioseal and monocone were 0.4 and 0.5 respectively, with no statistically significant difference. Meanwhile, the mean proportion of duration of obturation between GuttaFlow Bioseal and monocone were 134.3 and 143.9 respectively with no statistically significant difference. Conclusion: The sealing ability, the extrusion and the duration of obturation between Guttaflow Bioseal and monocone were comparable.